Power and the pulpit in Puritan New England - Elliott, Emory, 1942-2009 (Princeton legacy library., 1975)
For years, scholars have attempted to understand the powerful hold that the sermon had upon the imagination of New England Puritans. In this book Emory Elliott puts forth a complex and striking thesis: that Puritan religious literature provided the myths and metaphors that helped the people to express their deepest doubts and fears, feelings created by their particular cultural situation and aroused by the crucial social events of seventeenth-century America.